Hubungan Antara Self-Esteem Dengan Celebrity Worship Pada Dewasa Awal Penggemar K-Pop di Platform X - Nadhira, Lathifa Syafa; Savira, Siti Ina (INCARE, International Journal of Educational Resources, 2024)
The development of K-Pop Culture allows the emergence of the phenomenon of idol or celebrity worship among K-Pop fans, especially on Platform X. Data in Indonesia shows that celebrity worship is still found in early adulthood, contrary to the general view that this behavior decreases with age. Self-esteem is one of the factors associated with celebrity worship, where self-esteem is used as a variable in several studies related to its relationship with celebrity worship. However, there are inconsistencies in the results of previous studies regarding the relationship between self-esteem and celebrity worship. This study aims to investigate the relationship between self-esteem and celebrity worship in early adult K-Pop fans on Platform X. The approach used in this study is a quantitative approach involving 279 early adult respondents who are K-Pop fans on Platform X. The research data were analyzed using product moment correlation. The research data were analyzed using product moment correlation with a correlation value obtained of 0.177 (r=0.177) and a significance value of 0.003 (sig.<0.05). These results mean that there is a relationship between self-esteem and celebrity worship in early adult K-Pop fans on Platform X.